Semianalytical Threshold Voltage Model of a Double-Gate Nanoscale RingFET for Terahertz Applications in Radiation-Hardened (Rad-Hard) Environments - Singh K.; Kumar S.; Tiwari P.K.; Yadav A.B.; Dubey S.; Jit S. (My University, 2025)
In this work, a recent device structure called double-gate (DG) nanoscale RingFET has been investigated by developing a computationally efficient foremost semianalytical threshold voltage model. Poisson’s equation has been solved using parabolic approximation to calculate surface channel potential, which has been further employed to formulate the threshold voltage of the device. This device comes under the category of edgeless transistor, which has a lot of scope in radiation harsh environment-based applications. A cutoff frequency of terahertz range up to 1.1 THz has been observed in this device, which makes it very useful for high-frequency applications. The proposed model results are extensively verified with the simulation data obtained with a three-dimensional technology computer-aided design (3D TCAD) simulator from SILVACO ATLAS™. Both the modeled and simulated results are found to be in good agreement. © 2019, The Minerals, Metals & Materials Society.